2019
DOI: 10.2147/cmar.s222708
|View full text |Cite
|
Sign up to set email alerts
|

<p>Isovitexin Suppresses Cancer Stemness Property And Induces Apoptosis Of Osteosarcoma Cells By Disruption Of The DNMT1/miR-34a/Bcl-2 Axis</p>

Abstract: BackgroundIsovitexin (apigenin-6-C-glucoside, ISOV) is a natural flavonoid that exhibits tumor suppressive activity on various types of cancer. However, it is unknown whether the mechanism of its action in osteosarcoma (OS) is associated with epigenetic regulation and whether it involves DNA methyltransferase 1 (DNMT1), microRNAs and their targets.Materials and methodsThe present study investigated the effects of ISOV on DNMT1 activation and miR-34a and Bcl-2 expression levels in order to explain the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…In the osteosarcoma model, isovitexin further induced apoptosis and caused epigenetic regulation through the DNA methyltransferase 1 (DNMT1)/miR-34a/Bcl-2 axis, causing the suppression of stemness and inducing apoptosis in the spheres derived from osteosarcoma cells. Isovitexin also decreased tumor growth and size in a murine xenograft model [401]. In liver cancer, isovitexin decreased sphere and colony formation rates and stemness-associated markers by downregulating FoxM1 via inhibition of MnSOD.…”
Section: Vitexin and Isovitexinmentioning
confidence: 86%
See 1 more Smart Citation
“…In the osteosarcoma model, isovitexin further induced apoptosis and caused epigenetic regulation through the DNA methyltransferase 1 (DNMT1)/miR-34a/Bcl-2 axis, causing the suppression of stemness and inducing apoptosis in the spheres derived from osteosarcoma cells. Isovitexin also decreased tumor growth and size in a murine xenograft model [401]. In liver cancer, isovitexin decreased sphere and colony formation rates and stemness-associated markers by downregulating FoxM1 via inhibition of MnSOD.…”
Section: Vitexin and Isovitexinmentioning
confidence: 86%
“…When combined with doxorubicin and sorafenib, vitexin had apoptotic effects [405]. Isovitexin had antiproliferative effects in prostate cancer cells and osteosarcoma cells [400,401]. In the osteosarcoma model, isovitexin further induced apoptosis and caused epigenetic regulation through the DNA methyltransferase 1 (DNMT1)/miR-34a/Bcl-2 axis, causing the suppression of stemness and inducing apoptosis in the spheres derived from osteosarcoma cells.…”
Section: Vitexin and Isovitexinmentioning
confidence: 99%
“…For example vitexin or isovitexin show a number pharmacological properties, however, the most promising seems to be their anticancer activity. [7][8][9][10] Vicenin-2 is known to show hepaprotective, anticancer and antiinflammatory activities. [11][12][13][14] A large variety of Prunus species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated protective effects of IVX on inflammatory-related diseases like Alzheimer’s disease, 36 neuroinflammation, 37 osteosarcoma, 38 and liver cancer. 39 To test IVX-induced protection of OA, isolated chondrocytes were exposed to a range of working and non-toxic IVX concentrations.…”
Section: Discussionmentioning
confidence: 99%